Knowledge networks in science-based start-ups : actors and strategies - Sousa, Cristina (2012)
The paper investigates the strategic choices made by young science-based firms’ regarding the selection of knowledge sources. Drawing on two streams of research – on alliances and on social networks – two different dimensions of this strategy are considered: the activation of the entrepreneurs’ social capital and the intentional inclusion of new knowledge sources. The data collected for a subset of the Portuguese biotechnology sector are analysed with a view to answer to three research questions: i) To what do extent firms’ rely on entrepreneurs’ personal networks, activating their social capital to access scientific and technological knowledge at start-up; ii) To what extent are new actors added to knowledge networks at start-up; iii) Are there differences between existing and new ties in terms of strength and formalisation. The results obtained confirm the consideration of the strategies underlying network building is vital for an understanding of the configuration of young science-based firms’ knowledge networks. They reveal the existence of different knowledge network building strategies that often combine tie persistence with search for novelty. They also suggest that differences in the network building strategies may be the behind the somewhat contradictory results presented in the literature about the network configuration that is more favourable for innovation.